The Dynamics of Arabic Linguistic Variation - Hamdy, Mohammad Zainal; Mubayyinah, Mubayyinah (Al-Wazan: Journal of Arabic Education, 2025)
Arabic is one of the official languages recognized by the United Nations and serves as the national language in many countries across West Asia and North Africa. Beyond its political role, Arabic has historically functioned as a language of education, science, and religion. In Indonesia, the teaching of Arabic began with the spread of Islam, positioning it as the language of high prestige among Muslims since it acts as the medium of transmission for Islamic knowledge. Consequently, Arabic has become a priority language within Islamic education, particularly in pesantren and specialized language centers. However, the use of Arabic in non-native environments inevitably leads to variations, both in oral and written forms, as learners adapt the language according to their level of exposure and interaction. This study aims to investigate the phenomenon of linguistic variation in Arabic usage within Markaz Lughah Al-‘Arabiyah, a learning environment where students from diverse backgrounds engage with Arabic in formal and informal contexts. The research employs a qualitative method, utilizing natural settings to interpret the variations in language use, supported by observation, interviews, and document analysis. The findings reveal that linguistic diversity at the center manifests in code-switching, simplification of grammatical structures, and creative adaptations in oral communication. In writing, learners often exhibit a blend of classical and modern expressions, reflecting both challenges and innovations. The contribution of this study lies in providing insights into how Arabic develops in non-Arabic-speaking contexts, offering implications for Arabic pedagogy, curriculum design, and sociolinguistic studies